Analytical evaluation of shear link capacity in EBF: Beam-truss action analogy - Abdullah Alghossoon; Suhib Almarashdeh; Muhannad Alasiri; Ahmad Tarawneh (Results in Engineering)
This study introduces a simple analogical method to predict the ultimate shear-link strength of the eccentrically braced steel frame (EBF) system. Prior research highlighted the discrepancies between measured and predicted shear link strength in existing design codes and literature, referred to as overstrength ratio Ω. For this purpose, beam action analogy (BAA) and truss action analogy (TAA) are developed and verified using the most up-to-date and comprehensive database in the literature. The surveyed database comprises 200 specimens, including W-rolled and built-up sections with a wide range of material and cross-section properties. The research results demonstrate that the proposed analytical method significantly improves prediction accuracy, reducing unnecessary conservatism and offering an alternative model to the approaches outlined in the current design codes and the literature. The statistical evaluation of the measured-to-experimental ratio shows that the proposed model significantly surpasses the accuracy of the current design equations with a mean of 1.0, coefficient of variance of 0.16, and mean average percentage error of 1.6 %. Consequently, the study encourages the incorporation of this newly developed method as a prudent approach for more accurate analysis, and cost-effective, and resilient structural systems.